(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article Methods of teaching mathematics in elementary grades. Mathematics in elementary school should prepare students well for further mathematical education in secondary school, this gives students possession of a certain amount of mathematical knowledge and skills that will give them the opportunity to successfully study mathematical disciplines further at a more complex level.